Studi diskriptif penguatan literasi dan numerasi kelas VI SD Sabdodadi Keyongan Bantul - Ardian Arief; Nur Astuti; Abdul Rahim; Taryatman Taryatman; Trio Ardhian (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
This study aims to describe the strengthening of literacy and numeracy used by teachers in learning activities at SD Sabdodadi Keyongan Bantul. This research was conducted at SD Sabdodadi Keyongan Bantul, the source of the data was taken using purposive sampling technique. Data collection techniques used semi-structured interview techniques, frank observation techniques and documentation. Test the credibility of the data using source triangulation techniques and triangulation techniques. Data analysis techniques in this study were carried out through data collection, data reduction, data presentation, and decision making or verification. The results of this study indicate that literacy and numeracy strengthening can be done by teachers to achieve student learning skills through 1) The implementation of making it possible to read non-text books for 15 minutes and inserting literacy and numeracy in all learning units, making plans for strengthening literacy and numeracy by adjusting the reinforcement guidebook. literacy and numeracy from the Ministry of Education and Culture and carry out diagnostic tests so that teachers can adjust to the goals to be achieved. 2) The supporting factors are in the form of support from the school supervisory service or cooperation from students' parents as a means of supporting the implementation of literacy and numeracy strengthening in schools. 3) The inhibiting factors faced by teachers are in the form of limited facilities, infrastructure, limited time in learning, student knowledge is still low so that the literacy and numeracy strengthening process cannot run optimally. Efforts to overcome the inhibiting factors that can be done by teachers are in the form of using technology as an online or offline-based learning media in learning, participating in literacy and numeracy strengthening training, as well as working with teacher working groups to improve skills in preparing lesson plans.